Are hand preference and sexual orientation possible predicting factors for finasteride adverse effects in male androgenic alopecia?. Issue 7 (19th May 2016) - Motofei, Ion G.; Rowland, David L.; Georgescu, Simona R.; Tampa, Mircea; Baleanu, Bogdan C.; Paunica, Stana
Abstract: Sexual side effects of finasteride seem to be redoubtable, being encountered not only during therapy but also after treatment cessation. Consequently, any possible clinical/paraclinical elements that might predict these adverse effects would be useful in the selection of a therapeutic strategy for male androgenic alopecia. Previous published studies show that some compounds that interfere with sexual hormones can decrease sexual activation and response, according to hand preference (as reported for finasteride and tamoxifen) and according to sexual orientation (as noted for bicalutamide). Our preliminary published data and the arguments presented here suggest that these two individual parameters might be used by dermatologists in the therapeutic approach of male androgenic alopecia, so as to alert specific subsets of men, prior to treatment, of the potential increased risk for developing adverse effects to finasteride.